Notes on the traditional uses of Pterospartum tridentatum (L.) Willk. in Portugal - Almeida, Renata (2024)
In Portugal, the flowers, stems and roots of Pterospartum tridentatatum (L.) Willk [= Genista tridentata L.], a species native to the Iberian Peninsula and northwest Africa, have been used in traditional medicine as antioxidant, anti-diabetic and anti-inflammatory. Other historical and contemporary uses include culinary, to add a rustic touch to meat and rice, fuel and firelighter. In the city of Porto, its use as firelighter gave rise to a commercial activity, between the late 19th and mid-20th centuries, in which women played a central role.